Agama Lokal dan Agama Samawi di Indonesia: Kontestasi dan Akulturasi dalam Pembentukan Identitas Keagamaan - Luqman Musytarif; Hasan Bakti; Moh. Anwar Fadhlin (Yayasan Albahriah Jamiah Indonesia, 2025)
Understanding the dynamics of the relationship between local and heavenly religions in Indonesia is crucial in the context of pluralism and the complex formation of national religious identity. The long history of interaction between these two religious traditions demonstrates that the religious identity of Indonesian society was not born singularly, but rather is the result of encounters, negotiations, and transformations that took place across time and space. This study aims to explain how the process of contestation and acculturation between local and heavenly religions plays a significant role in shaping the construction of a distinctive religious identity in Indonesia. The research method uses a qualitative approach with historical, sociological, and anthropological analysis through in-depth literature studies and contextual observations of community religious practices and symbols. The results show that the historical dynamics of the relationship between the two demonstrate a pattern of contestation in the form of a struggle for religious authority and the interpretation of sacred values that reflect the hegemonic efforts of heavenly religions over local traditions. However, on the other hand, a productive acculturation process occurs through the integration of symbols, rites, and spiritual values that allow local religions to transform without losing the essence of their identity. This acculturation is evident in syncretic practices, social rituals, and ethical values that enrich the community’s religiosity. These findings show that Indonesian religious identity is formed through a dynamic negotiation process between contextual local values and the universal values of the heavenly religions, resulting in a religious pattern that is inclusive, adaptive, and has a distinctive Nusantara character.